Walrasian equilibrium in large, quasi-linear markets - E. Glen Weyl; Alexander White; Eduardo M. Azevedo (Theoretical Economics, 2013)
In an economy with indivisible goods, a continuum of agents and quasilinear utility, we show that equilibrium exists regardless of the nature of agents' preferences over bundles. This contrasts with results for economies with a finite number of agents, which require restrictions on preferences (such as substitutability) to guarantee existence. When the distribution of preferences has full support, equilibrium prices are unique.
Keywords: D51; 330; Walrasian equilibrium; quasilinear utility; indivisible goods; continuum economies; complementary preferences